Takayasu's arteritis causing coronary stenosis with myocardial ischemia, severe aortic regurgitation, and pericarditis - Ana Álvarez Vázquez, MD; Julia López Alcolea, MD; Javier Urmeneta Ulloa, MD, PhD; Alberto Forteza Gil, MD; Jorge Rivas Oyarzabal, MD; José Ángel Cabrera Rodríguez, MD, PhD; Manuel Recio Rodríguez, MD, PhD; Gonzalo Pizarro Sánchez, MD; Vicente Martinez de Vega, MD (Radiology Case Reports)
Takayasu's Arteritis (TA) is a rare, chronic large-vessel vasculitis that can lead to severe cardiac complications and life-threatening outcomes. Early diagnosis is essential for improving patient prognosis, but its nonspecific clinical presentation and laboratory findings often cause delays. We present a 34-year-old woman with a history of heart murmur who presented with chest pain but no additional symptoms. Imaging revealed aortic regurgitation, ventricular septal defect, myocardial ischemia, pericarditis, aortic wall thickening, and multivessel stenoses, leading to a diagnosis of Takayasu's Arteritis, treated with coronary bypass and aortic tube graft surgery. Takayasu's Arteritis should be included in the differential diagnosis of patients presenting with atypical clinical features and cardiac involvement, particularly in cases with valvular disease. This case highlights the essential role of multimodal imaging in the detection and management of TA.